The Effect of Body-Weight Squat Exercise on Increasing Lower-Limb Muscle Strength and Reducing the Risk of Falls in Elderly Women - Govinda Vittala; Ni Luh Nopi Andayani; Ni Luh Putu Gita Karunia Saraswati (Indonesian Journal of Global Health Research, 2026)
The decline in estrogen levels among elderly women leads to increased bone fragility and joint degeneration, making them more susceptible to osteoporosis and osteoarthritis. One of the most serious consequences of reduced musculoskeletal function in older women is an increased vulnerability to falls. Therefore, to improve the quality of life of elderly women, it is essential to implement exercise programs that are easy to remember, simple to perform, safe, and feasible to conduct independently at home. This study aimed to determine the effectiveness of body-weight squat exercises in improving lower limb muscle strength and reducing the risk of falls among elderly women. This study employed an experimental design using a randomized controlled trial with a pre-test and post-test control group design. A total of 30 elderly women participated as samples and were randomly assigned into two groups: the intervention group and the control group. Participants in the intervention group performed body-weight squat exercises for four weeks, with a training frequency of four times per week. Outcome measures included lower limb muscle strength, assessed using the Five Times Sit-to-Stand Test (FTSTS), and fall risk, assessed using the Timed Up and Go Test (TUG). Measurements were taken before and after the intervention. The study was conducted in Mengwi District, Badung Regency, Bali, from July to September 2025. Data were analyzed using SPSS, based on the pre-test and post-test measurements. The statistical analyses employed were the Paired Sample T-Test and the Independent Sample T-Test. The results demonstrated a significant increase in lower limb muscle strength (p = 0.000) and a significant reduction in fall risk (p = 0.000) in the intervention group, as analyzed using the Paired Sample T-Test. Performing body-weight squat exercises four times per week for four consecutive weeks effectively increases lower limb muscle strength, as measured by the FTSTS test, and reduces the risk of falls, as measured by the TUG test, among elderly women in Gulingan Village, Mengwi District.